2012
DOI: 10.1155/2012/480609
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Evaluation of Deleterious SNPs in APOE Gene of Alzheimer’s Disease

Abstract: Introduction. Apolipoprotein E (APOE) is an important risk factor for Alzheimer's disease (AD) and is present in 30–50% of patients who develop late-onset AD. Several single-nucleotide polymorphisms (SNPs) are present in APOE gene which act as the biomarkers for exploring the genetic basis of this disease. The objective of this study is to identify deleterious nsSNPs associated with APOE gene. Methods. The SNPs were retrieved from dbSNP. Using I-Mutant, protein stability change was calculated. The potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…ApoE4 has been confirmed as an important factor for dementia and progress of cognitive impairment in the elderly [100,101]. ApoE protein, Aβ, and tau protein interact in a specific way, which may be the biological basis for ApoE effect on dementia development [102]. The ApoE ε4 allele polymorphism is an independent risk factor for MCI, and cognitive level in ε4 carriers is lower than noncarriers [103].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 99%
“…ApoE4 has been confirmed as an important factor for dementia and progress of cognitive impairment in the elderly [100,101]. ApoE protein, Aβ, and tau protein interact in a specific way, which may be the biological basis for ApoE effect on dementia development [102]. The ApoE ε4 allele polymorphism is an independent risk factor for MCI, and cognitive level in ε4 carriers is lower than noncarriers [103].…”
Section: Insulin Resistance and The Apoe ε4 Allelementioning
confidence: 99%
“…Larger stability decreases, however, were predicted only for the I585V and L653R variants. Discrepancies in the prediction results obtained from different in silico analysis tools are expected as shown in several similar studies [47], [48]. These are probably due to the overall limitations of in silico analysis and the limitations encountered, for instance, due to lack of structural or functional data for many proteins.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, these significant SNP could also be used to cluster different races, showing that these AD‐associated SNP represented different genomic backgrounds of the studied races. Differences in the prevalence of a disease, and carrier and genotype frequencies among racial groups are well known, and recent advances in genetic studies are very promising . Although the actual cause of AD has yet to be determined, many studies have reported that AD is most likely influenced by genetic factors.…”
Section: Discussionmentioning
confidence: 99%